Dipole fluctuation and structural phase transition in hydrogen-bonding molecular assemblies of mononuclear CuII complexes with polar fluorobenzoate ligands. Issue 39 (25th August 2021) - Takahashi, Kiyonori; Miyazaki, Yuji; Noro, Shin-ichiro; Nakano, Motohiro; Nakamura, Takayoshi; Akutagawa, Tomoyuki
Abstract : An effective approach to construct dynamic motional space in molecular crystals is accomplished by combining hydrogen-bonding chains with dipole–dipole interactions in mononuclear Cu II complexes. Abstract : A series of mononuclear Cu II complexes, [Cu II (4-FBA)2 (py)2 (H2 O)] (1 ), [Cu II (3-FBA)2 (py)2 (H2 O)] (2 ), and [Cu II (3, 4-F2 BA)2 (py)2 (H2 O)] (3 ), where 4-FBA = 4-fluorobenzoate, 3-FBA = 3-fluorobenzoate, 3, 4-F2 BA = 3, 4-difluorobenzoate, and py = pyridine, respectively, was synthesized and the complexes crystallographically identified. All the Cu II complex crystals share a one-dimensional O–H⋯O hydrogen-bonding chain substructure, although the mutual alignment of fluorinated benzoate (F x BA) ligands exhibits subtle differences among the various compounds, i.e., F x BA ligands align in an antiparallel fashion in crystals 1 and 3, while 3-FBA ligands in crystal 2 are interdigitated with a tilt along the a axis. Reversible phase transitions were found upon heating at 170.7, 171.3, and 267.5 K for crystals 1, 2, and 3, respectively; all crystals showed approximately 3% expansion and shrinkage of the intermolecular O–H⋯O hydrogen bond distances associated with the thermally activated orientational fluctuations of the F x BA ligands in crystals 1 and 3 . The increase in dielectric constant with increasing temperature, at 240 K, activated molecular fluctuation in the 3, 4-F2 BA ligands in crystal 3 . Heat capacity measurements indicated that both the expansion and shrinkage of hydrogen bonds, and the molecular fluctuation in 3, 4-F2 BA ligands, contributed to phase transition, and the latter caused dipole fluctuation, resulting in a dielectric anomaly in crystal 3 .